2011
DOI: 10.1097/acm.0b013e31822220c5
|View full text |Cite
|
Sign up to set email alerts
|

Toward Shared Decision Making: Using the OPTION Scale to Analyze Resident–Patient Consultations in Family Medicine

Abstract: Participating family medicine residents have not integrated SDM behaviors, which may also pertain to residencies elsewhere. Interventions are required to foster family medicine residents' practice of SDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 35 publications
6
46
2
Order By: Relevance
“…However, that degree of comfort may not exist for all specialties: a large, multispecialty study of residents and educators concluded that risk communication, an essential part of SDM, may not be receiving enough attention during graduate education. 39 Our results and the current literature [39][40][41] suggest that more training, for both residents and attendings, is likely warranted.…”
Section: Discussionsupporting
confidence: 56%
“…However, that degree of comfort may not exist for all specialties: a large, multispecialty study of residents and educators concluded that risk communication, an essential part of SDM, may not be receiving enough attention during graduate education. 39 Our results and the current literature [39][40][41] suggest that more training, for both residents and attendings, is likely warranted.…”
Section: Discussionsupporting
confidence: 56%
“…age, socioeconomic status); the clinician's experience or gender; preference misdiagnosis; or time pressures. The duration of the encounter is likely to be of consequence, as in primary care, longer consultations with general practitioners have coincided with higher level of SDM measured with the OPTION scale [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, these processes are not even minimally present in most clinical practice. 23 It might seem straightforward enough to ask a patient about his or her values and preferences, but the actual process of values clarification or preference elicitation is fraught with difficulties. For example, values and preferences have been shown to be highly unstable, and varying the method of asking a question can substantially change a patient's answer.…”
Section: Understandingmentioning
confidence: 99%